TECHNES: Penyedia Layanan Jasa Service Berbasis Aplikasi Android - M Syahid Nur Wahid; Ali Mirza Najafi; Alfaiz Sihaj; Rahel Alik; Asisah Az Zahrah Irsani (Sakura Digital Nusantara, 2023)
This article describes how the waterfall method approach was used for the creation of an Android app by Technes, an app-based service provider. The waterfall method is a methodical and linear approach to developing software that starts with analyzing requirements and progresses through design, testing, and implementation. In this article, we will discuss how the waterfall method was applied to the development of the Technes app to ensure it was well-organized and efficient. The waterfall methodology's requirements analysis, design, implementation, testing, and implementation phases are all thoroughly explained. Developing a solid understanding of the technical user requirements and deciding on the functionality that the app should have are the tasks involved in the requirements analysis process. An intuitive and responsive user interface is then produced during the design phase to enhance the user experience. The main concern of this article is how the waterfall methodology can help solve challenging problems when developing complex Android applications. We discuss many phases of the waterfall method such as requirements analysis, design, implementation, testing, and planning, and we illustrate how each stage contributes to the final outcome of the Technes application. The findings of the discussion show that the waterfall method can help organize, track, and evaluate each stage of app development in a clear and organized way. We also recognize the limitations of the waterfall method with respect to changing user requirements and backend operations, but these issues can be resolved with effective communication. The end result is a Technes application that fully meets user needs, has a responsive user agent, and offers a consistent user experience.